ChemInform Abstract: Chiral Phosphoric Acid Catalyzed Asymmetric Ugi Reaction by Dynamic Kinetic Resolution of the Primary Multicomponent Adduct. Issue 36 (August 2016) - Zhang, Yun; Ao, Yu‐Fei; Huang, Zhi‐Tang; Wang, De‐Xian; Wang, Mei‐Xiang; Zhu, Jieping
Abstract: Reaction of isonitriles with 3‐(arylamino)isobenzofuran‐1(3H)‐ones in the presence of a catalytic amount of an octahydro (R)‐binol‐derived chiral phosphoric acid affords 3‐oxo‐2‐arylisoindoline‐1‐carboxamides in high yields with good to high enantioselectivities.